2012
DOI: 10.1007/s11095-012-0774-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetised Thermo Responsive Lipid Vehicles for Targeted and Controlled Lung Drug Delivery

Abstract: The lipid system presented thermo-sensitive characteristics, suitable for controlled delivery, the model drug and SPION loaded lipid system was magnetically active and movable using simple permanent magnets, and the system demonstrates promise as an effective drug vehicle in targeted and controlled inhalation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…(7,8) In particular, a growing community of researchers has been investigating the potential for targeted aerosol delivery to specific lung regions using SPIONs in combination with target-directed magnetic gradient fields. (9,10) SPIONs can also serve as theranostic agents, i.e., as both diagnostic and therapeutic agents, where their inherent magnetic properties can provide image contrast in magnetic resonance imaging and thermal ablation in magnetic fluid hyperthermia therapy. (11) Moreover, as SPIONs can be chemically modified or engineered for simultaneous biomedical functions, their application as aerosolized chemotherapeutics may be used to increase drug dosage to the lungs while reducing systemic side effects.…”
Section: Introductionmentioning
confidence: 99%
“…(7,8) In particular, a growing community of researchers has been investigating the potential for targeted aerosol delivery to specific lung regions using SPIONs in combination with target-directed magnetic gradient fields. (9,10) SPIONs can also serve as theranostic agents, i.e., as both diagnostic and therapeutic agents, where their inherent magnetic properties can provide image contrast in magnetic resonance imaging and thermal ablation in magnetic fluid hyperthermia therapy. (11) Moreover, as SPIONs can be chemically modified or engineered for simultaneous biomedical functions, their application as aerosolized chemotherapeutics may be used to increase drug dosage to the lungs while reducing systemic side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Upadhyay et al [69] investigated the potential of nanoformulation with SPION and a drug within a lipid matrix as a potentially targetable and thermosensitive inhalable drug delivery system. The therapeutic nanoparticle was characterised by TRPS.…”
Section: Trps In Drug Delivery and Drug Development Applicationsmentioning
confidence: 99%
“…Although Dames et al determined dry powder formulations of SPIONs will not undergo magnetic direction, Upadhyay et al formulated drug and SPION containing lipid microparticles for dry powder inhaler based lung delivery [90]. Cascade impactor measurements showed that 30% of the inhaler-generated aerosol consisted of particles with a diameter < 2.5 µm, which would deposit deeper into the lungs.…”
Section: Respiratory Medicine Applications Of Spionsmentioning
confidence: 99%